1986
DOI: 10.2307/1130343
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prediction of Achievement and Attitudes in Mathematics and Reading

Abstract: The purpose of the longitudinal study was to investigate the prediction of children's academic achievement on the basis of cognitive tasks given prior to kindergarten, and academic attitudes on the basis of teachers' and mothers' ratings of the children's general cognitive abilities and actual achievement. Subjects were tested initially before entering kindergarten; from 105 to 154 of the 255 kindergarten children were followed through grades 1, 2, 3, 5, and 10. A subset of cognitive tasks maintained a high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
1
10

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(147 citation statements)
references
References 7 publications
9
127
1
10
Order By: Relevance
“…Research has shown that knowledge of mathematics in preschool correlates .46 with 10th-grade math achievement (Stevenson & Newman, 1986) and successfully predicts math achievement through age 15 years even after accounting for early reading, cognitive skills, and family and child characteristics (Watts et al, 2014). For many topics and abilities, initial knowledge predicts learning and later knowledge (Bransford, Brown, & Cocking, 2008;Jimerson, Egeland, & Teo, 1999;Thomson, Rowe, Underwood, & Peck, 2005;Wright, 1994).…”
Section: Early Mathematics Knowledgementioning
confidence: 99%
“…Research has shown that knowledge of mathematics in preschool correlates .46 with 10th-grade math achievement (Stevenson & Newman, 1986) and successfully predicts math achievement through age 15 years even after accounting for early reading, cognitive skills, and family and child characteristics (Watts et al, 2014). For many topics and abilities, initial knowledge predicts learning and later knowledge (Bransford, Brown, & Cocking, 2008;Jimerson, Egeland, & Teo, 1999;Thomson, Rowe, Underwood, & Peck, 2005;Wright, 1994).…”
Section: Early Mathematics Knowledgementioning
confidence: 99%
“…It has been suggested that parents' involvement has a significant impact on students' attitudes towards mathematics, students' achievement in mathematics (Stevenson and Newman, 1986;Tocci and Engelhard, 1991), as well as gender difference in mathematics (Eccles and Jacobs, 1986;Tiedeman, 2000).…”
Section: On Mathematics Learningmentioning
confidence: 99%
“…Phillips (1987) and Stevenson and Newman (1986) reported that children who perceive themselves as less competent have parents with much fewer expectations concerning their success. Children's perception of their parents' expectations appears to directly influence the children's self-attribution of competence, as well as their involvement in learning tasks.…”
Section: Children 'I' Characteristicsmentioning
confidence: 99%